Challenges and responses of China’s energy legal system under the double carbon target - Huang, Lansong; Wei, Xuezhi; Wang, Quansheng (Frontiers in Energy Research, 2023)
The deep-seated problem of carbon neutrality is the energy problem, and the change in energy consumption structure determines the degree of achieving China's double carbon target. The basic path to achieve the dual carbon goal is to realize the rule of law in energy governance, and the premise of the rule of law in energy governance is to establish a perfect energy legal system. However, there are also problems such as the dilemma of energy law structure, the lack of dual-carbon legislative goals, the dilemma of legal coordination, the lack of basic framework laws, and the disconnection between energy laws and energy policies, etc. To remedy these dilemmas and shortcomings, the path of constructing a perfect energy law and regulation system is to: establish a Chinese energy development plan with dual-carbon goals To make up for these dilemmas and shortcomings, the following is the path options: to establish China's energy development plan and energy legislation plan for the dual-carbon goal; to formulate a basic energy law to lay the framework of China's energy legal system under the dual-carbon goal; to establish the concepts and principles of energy legislation under the dual-carbon goal as the basis for maintaining a coordinated and unified energy legal system; to adopt a "parcel" legislative model to formulate and revise energy laws to fill in the gaps; and to promote energy policies and energy laws in parallel to promote energy policies. Adopt a "wraparound" legislative model to formulate and revise energy laws and fill in the gaps; promote the legalization of energy policies in parallel with energy laws.